Dental anomalies in craniofacial microsomia: A systematic review. (28th October 2019) - Elsten, Eline E. C. M.; Caron, Cornelia J. J. M.; Dunaway, David J.; Padwa, Bonnie L.; Forrest, Chris; Koudstaal, Maarten J.
Abstract: Objective: To provide an overview on the prevalence and types of dental anomalies in patients with craniofacial microsomia (CFM). Eligibility criteria: Inclusion criteria were CFM and dental anomalies. The following data were extracted: number of patients, methodology, mean age, sex, affected side, severity of mandibular hypoplasia, dentition stage and dental anomalies. Information sources: Cochrane, EMBASE, PubMed, MEDLINE Ovid, Web of Science, CINAHL EBSCOhost and Google Scholar, searched until the 30 August 2019. Risk of bias: The quality was examined with the OCEBM Levels of Evidence. Included studies: In total, 13 papers were included: four retrospective cohort studies, four prospective cohort studies, four case‐control studies and one case series. Synthesis of results: The studies reported information on dental agenesis, delayed dental development, tooth size anomalies, tooth morphology and other dental anomalies. Description of the effect: Dental anomalies are more often diagnosed in patients with CFM than in healthy controls and occur more often on the affected than on the non‐affected side. Strengths and limitations of evidence: This is the first systematic review study on dental anomalies in CFM. However, most articles were of low quality. Interpretation: Dental anomalies are common in CFM, which might be linked to the development of CFM. The pathophysiology of CFM is not entirely clear, and further research is needed.